2016
DOI: 10.1186/s12872-016-0348-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk of bleeding after hospitalization for a serious coronary event: a retrospective cohort study with nested case-control analyses

Abstract: BackgroundBleeding events have been associated with the use of antiplatelet agents. This study estimated the incidence of bleeding events in patients previously hospitalized for a serious coronary event and determined the risks of bleeding associated with the use of acetylsalicylic acid (ASA) and/or clopidogrel.MethodsA UK primary care database was used to identify 27,707 patients aged 50 to 84 years, hospitalized for a serious coronary event during 2000 to 2007 and who were alive 30 days later (start date). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
1
10
0
1
Order By: Relevance
“…55,56 In a recent large cohort study which included 27,707 patients, Gonzalez-Perez et al concluded that 73% of patients with upper gastrointestinal bleeding and 23% of those with lower gastrointestinal bleeding, being on antiplatelet therapy for a serious coronary event, needed hospitalization. 57 In an observational study which included 122 patients, DAPT was associated with a significant decrease of hemoglobin levels (1.6, 95% CI: 1.2-1.8, p <0.001) and an increased prevalence of anemia after DAPT (9.1% vs. 45.9%).…”
Section: Anemia Following Gastrointestinal Bleeding -A Precipitating mentioning
confidence: 97%
“…55,56 In a recent large cohort study which included 27,707 patients, Gonzalez-Perez et al concluded that 73% of patients with upper gastrointestinal bleeding and 23% of those with lower gastrointestinal bleeding, being on antiplatelet therapy for a serious coronary event, needed hospitalization. 57 In an observational study which included 122 patients, DAPT was associated with a significant decrease of hemoglobin levels (1.6, 95% CI: 1.2-1.8, p <0.001) and an increased prevalence of anemia after DAPT (9.1% vs. 45.9%).…”
Section: Anemia Following Gastrointestinal Bleeding -A Precipitating mentioning
confidence: 97%
“…As summarized in Supplementary Figure 1, a multistage process was undertaken to confirm the recorded diagnosis of UGIB or LGIB or unspecified GIB, involving at least 1 of the following validation processes: crosschecking with cases validated in previous studies, [21][22][23][24] linkage to HES data, and manual review of patient EMRs including free-text comments and data mining using text strings (see Supplementary Methods). Potential incident UGIB or LGIB cases were considered confirmed if there was evidence or referral to a consultant or hospitalization.…”
Section: Validation Of Ugib and Lgib Casesmentioning
confidence: 99%
“…Fourthly, the recorded UGIB or LGIB diagnoses were validated through a multistep process, including linkage to hospitalization data or through manual review of patient records in THIN including the free text comments. Previous validation studies using questionnaires to PCPs as the gold standard have shown UGIB and LGIB Read codes in THIN to have PPVs of 95% and 82%, respectively [21][22][23][24] after manual review of medical records incorporating free text comments. A limitation of our study is that misclassification of low-dose aspirin could have occurred from individuals discontinuing their preventative treatment during follow-up-in censoring follow-up at 1 year after start of therapy, GI bleeding rates were slightly higher.…”
Section: Almost Three-quarters Ofmentioning
confidence: 99%
“…To prevent such an excessive thrombotic event, anti‐platelet medication is given to patients before and after the endovascular implantation of metallic devices. The anti‐thrombotic medication carries the risk of spontaneous bleeding in organs such as brain and gastrointestinal tract . Therefore, it would be beneficial if the anti‐thrombotic medication is removed and a rapid endothelialization of the endovascular metallic devices is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-thrombotic medication carries the risk of spontaneous bleeding in organs such as brain and gastrointestinal tract. 5,6 Therefore, it would be beneficial if the anti-thrombotic medication is removed and a rapid endothelialization of the endovascular metallic devices is achieved.…”
Section: Introductionmentioning
confidence: 99%